Research on the habits, attitudes and motivations underlying craft food choice by consumers in Ukraine - Dudarev, Igor (Lutsk : LNTU, 2024)
The number of craft food producers in Ukraine is also growing, but the craft food market is still understudied. Therefore, the purpose of the research was to study through a survey the habits, attitudes and motivations that determine the choice of craft food products by consumers in Ukraine. The survey was conducted in two regional centers of Ukraine – Lutsk and Mykolaiv – among consumers of different age, gender, income levels and education levels. About 84.3% of the respondents are consumers of craft food. Respondents indicated that they buy craft food periodically and occasionally. Most consumers believe that craft food is tastier and of better quality than mass-produced food. Respondents noted that craft foods are more expensive than mass-produced foods, but 29% of respondents are willing to pay 10% extra for them. The most popular craft food products among Ukrainian consumers were identified, including baked goods, confectionery, meat and dairy products. Ukrainians buy craft food mainly directly from producers, in chain and specialised stores. Respondents indicated that they do not have enough information about craft food producers and their products. They would like to see more craft food advertising on online resources. Thus, the results of the survey made it possible to determine the habits and attitudes of Ukrainian consumers regarding craft food, as well as to investigate the motives leading to its purchase. The obtained results will be useful for producers of craft foods, as they will allow them to create a profile of the consumer of their products and to make the information about their products more effective.
Keywords: local foods; craft producers; consumer preferences; craft food market; consumer survey